The Routledge history of East Central Europe since 1700 - Livezeanu, Irina HerausgeberIn; Klimó, Árpád von 1964- HerausgeberIn (The Routledge histories, 2017)
"Covers territory from Russia in the east to Germany and Austria in the west, exploring the origins and evolution of modernity in this region"--Provided by the publisher